2022
DOI: 10.6007/ijarbss/v12-i7/14053
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Perceived Business Performance among Private Business Organizations: A Partial Least Square Approach

Abstract: This study is very important to ensure that business organizations can formulate and plan a strategic plan to continue to ensure that their business performance remains viable and sustainable. The aim of this study is to assess the direct relationships between corporate image, employee engagement, organizational culture, employee loyalty, and business performance among private business organizations. This study is vital to be carried out because many private organizations face difficulty to maintain their busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A study conducted on bank customers in Nigeria by Adeniji et al (2015) showed that employee loyalty has a significant mediating effect on the relationship between corporate image and business performance. Osman et al (2022) in their study of 329 employees in the private sector have found that corporate image and organizational culture have a positive and significant direct influence on employee loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted on bank customers in Nigeria by Adeniji et al (2015) showed that employee loyalty has a significant mediating effect on the relationship between corporate image and business performance. Osman et al (2022) in their study of 329 employees in the private sector have found that corporate image and organizational culture have a positive and significant direct influence on employee loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Osman and Sentosa (2013), the most effective way to increase employee loyalty is to make employees feel that their presence in the organization is significant. Osman et al (2022) stated that feedback systems from employees can help increase employee loyalty by providing two-way communication between employees and management. If employees feel that the organization listens to their views and recognizes their contribution to the organization, the employees will be more loyal and in turn, will contribute to the organization's business performance.…”
Section: Employee Loyaltymentioning
confidence: 99%